EFEKTIFITAS KONSUMSI JANTUNG PISANG BATU (MUSA BALBISIANA COLLA) TERHADAP PRODUKSI ASI PADA IBU POST PARTUM DI WILAYAH KERJA PUSKESMAS MESKOM - Yunnarli, Yunnarli; Lisviarose, Lisviarose; Mardiya, Rizka; Tanberika, Fajar Sari (Ensiklopedia of Journal, 2025)
Breast milk (ASI) contains nutrients according to the baby's needs for growth, immunity, preventing various diseases and for the baby's intelligence. Banana flower is one of the plants containing lactagogum which can stimulate the hormones oxytocin and prolactin. The purpose of this study was to determine the Effectiveness of Consumption of Batu Banana Flower (Musa Balbiana Colla) on Breast Milk Production in Postpartum Mothers in the Meskom Health Center Work Area. The research design was pre-experimental with One Group Pretest-Posttest. The sampling technique used Accidental sampling with a population of postpartum mothers with a sample size of 17 respondents. Breast milk production before consuming boiled banana flower from 17 respondents was (64.07%) sufficient breast milk production, (23.5%) insufficient breast milk production and (11,8%) high breast milk production. Breast milk production after consuming boiled banana flower was (94,1%) high breast milk production and (5,9%) low breast milk production. There is an effect of Banana Heart Consumption (Musa Balbisiana Colla) on Breast Milk Production in Postpartum Mothers with a p-value = 0.000. It is recommended that giving stone banana blossoms (Musa Balbisiana Colla) can help increase breast milk production for post partum mothers on days 1-5 and it is hoped that Meskom Community Health Center midwives can promote stone banana blossoms (Musa Balbisiana Colla) to post partum mothers to facilitate breast milk production and increase education. and mother's motivation to breastfeed exclusively to improve maternal and child health.Keywords: Breast Milk Production, Banana Heart Stone, Post Partum.